Purification and characterization of extracellular lipase from Candida cylindracea using palm oil mill effluent supplemented medium - Alam, Md. Zahangir; Salihu, Aliyu; Abdul Karim, Mohamed Ismail; Hamzah, Mohd. Salleh (2011)
Production of Candida cylindracea lipase was optimized and highest lipase production was achieved after 36 hr of fermentation using palm oil mill effluent supplemented medium. The extracellular lipase was purified by DEAE-sepharose and Sephacryl S-200, exhibiting a single band with molecular mass of 58 kDa by SDS-PAGE and gel filtration. The temperature and pH optima of the enzyme were found to be 35oC and 8 respectively. The enzyme was stable at pH 7.0 and 8.0 for 12 hr and also at temperature range of 25 to 35oC for 1 hr. Among the divalent cation salts tested on the lipase activity, Ca2+ and Mn2+ activated the enzyme most, while Cu2+ and Fe2+ inhibited it. Non-ionic (Tween-80 and Tween-20 and Triton X-100) and ionic detergents (SDS) at 1% appeared to have stimulatory and inhibitory effects on lipase activity respectively. In case of stability in organic solvents, water miscible solvents are concentration dependent; where their low concentrations showed some stimulatory effects, with marked inhibition at higher concentrations. It can be concluded that knowledge of these properties of the enzyme as described in this study could go a long way in its effective utilization for industrial application processes.